Estudo de associação do polimorfismo de base única no códon 72 do gene humano p53 e as características de pigmentação - COSTA, Kárita Antunes (2010)
The p53 gene encodes a protein which has various functions such as monitoring of the cell cycle, role in repair mechanisms and apoptosis. New functions performed by this protein have been observed and studied as acting in the cascade of skin pigmentation by acting as transcription factor for genes important in this process as POMC (pro-opiomelanocortin) and MC1R (melanocortin receptor 1). Among the genetic polymorphisms, the codon 72 p53 gene is the most commonly studied and this variant has been associated with increased risk for various cancers, including skin. However, the association between this and other types of cancers has generated controversial results. The polymorphism occurs in a substitution G / C codon 72 p53 gene resulting in a change of amino acid sequence (CGC to CCC for arginine and proline). This polymorphism occurs in areas rich in proline generating morphophysiological changes as well as a difference in electrophoretic mobility of the protein. The aim of this study was to establish a possible association between the codon 72 polymorphism of p53 gene with the characteristics of pigmentation such as skin color, hair, eye and skin response after exposure to sunlight (reddening or bronze). The 96 healthy volunteers were recruited randomly and information on skin color, ability to tan and other characteristics of pigmentation were collected through a standardized questionnaire. Genomic DNA was extracted from venous blood and genotyping was performed by polymerase chain reaction (PCR). The polymorphism was investigated by photo documentation after agarose gel electrophoresis. Samples that generated doubts were confirmed by digestion with sitespecific action of the restriction enzyme BstUI. Allele frequencies of 96 volunteers to p53Arg/72 and p53Pro/72 were 67.70% and 32.30% respectively. Genotype frequencies for Arg / Arg, Arg / Pro and Pro / Pro were 50.00% 35.40% 14.60% respectively. We did not detect a significant association between reddening or tanning after sun exposure with the polymorphism (p = 0.678), on the other hand we observed an association between the genotype Pro / Pro and blue eyes / green (p = 0.01) among showing redness of the skin, demonstrating a disadvantage in relation to the sun when there is occurrence of this specific phenotype (eye color) combined with the genotype Pro / Pro.